POTENSI PEMANFAATAN BIOMASSA SEKAM PADI UNTUK PEMBANGKIT LISTRIK MELALUI TEKNOLOGI GASIFIKASI - Redaksi Tim Jurnal (Energi & Kelistrikan, 2017)
Energy consumption in Indonesia from year to year has increased significantly and this must be realized by the whole community. While the national energy reserves will be increasingly thinner so must be found new energy reserves. One of the most potential energy in Indonesia is biomass. Therefore, it is necessary to make various breakthrough in utilizing biomass, one of potency of biomass utilization is gasification. Therefore, it is necessary to make various breakthrough in utilizing biomass, one of potency of biomass utilization is gasification. As an agricultural country, Indonesia produces large quantities of biomass. One of the agricultural waste is rice husk, the weight of husk produced is 22% from the weight of dry milled grain. The availability of rural biomass has the potential to be used in power generation in areas not covered by electricity services.